Qur’anic prerequisites for developing scientific mind - Gilani, Sayyid Muhammad Yunus; Islam , Tajul (International Islamic University Malaysia, 2011)
Islamic science has a glorious past and it successfully contributes to the development of modern science. The emergence, developments and accomplishments of Islamic scientific trend are traced back to the advent of Islamic era when human mind had been radically reformed, and transformed from its irrational and superstitious tendency into a scientific nature. There are overwhelming emphases given in the Qur’an on shaping a scientific mind. In order to achieve this aim, the Qur’an follows many unique methods, such as denying supposition in the place of conviction, disobeying caprice and emotions in place of knowledge, discouraging blind imitation of forefathers and chieftains, developing consciousness, employing deductive reasoning, approaching the doctrine of cause and effect, posing enlightening questions, developing deep and critical thinking instead of superficial outlook. However, in the context of modern approaches of shaping the scientific mind, the three approaches of the Qur’an namely; making mind conscious, developing capacity of objective judgment and conscious reasoning should be scrutinized and researched.